Chemistry the molecular nature of matter and change - Silberberg, Martin ([S.l.] : Mosby-Year Book, 1996)
This general chemistry text centres on the theme that observable change in chemical systems is the result of molecular change. The aims of this edition are to enable students to perceive matter and change at the molecular level and to help build student confidence in their ability to solve chemical problems as they discover the relevance of chemistry to their lives.
Keywords: chemistry,molecular,nature,matter